(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background Urodynamics provide objective pathophysiological explanations for symptoms and/or dysfunction of the lower urinary tracts. It reproduce patient symptoms during the performance of the study and assist clinicians in determining the precise cause, aid in diagnostic process and follow up of patients with urinary incontinence. Objective To evaluate the role of urodynamic study in confirming the diagnosis of urinary incontinence in Iraqi women. Differentiate the types of urinary incontinence and assess the importance of risk factors in its development. Methods This study was performed in the Urology Department, Al-Sader Medical City, Holly Najaf between March 2013 and March 2014. One hundred and twenty female subjects aged 20 to 60 years were studied. They comprised 60 patients and 60 control subjects. Medical history, clinical examination and urodynamic tests were performed for them. Result Thirty four patients presented with stress urinary incontinence, nineteen with urge type, five with mixed type and only two patients presented with overflow urinary incontinence. The patients were complaining of cough, constipation (most of them in stress type) and presence of cystocele (most of them in stress urinary incontinence patients). In addition, there was positive history of hypertension and positive family history of urinary incontinence. The strong desire to urination and the maximum urinary bladder capacity of patients was significantly smaller than those of control subjects, specifically those patients with stress and urge urinary incontinence. Conclusion Age, Parity and body mass index significantly affect the prevalence of urinary incontinence in women who have given birth vaginally. Stress urinary incontinence is the most common type of UI among women regardless the small sample size in the study. Cystometric changes of urodynamic study were markedly evident in the stress urinary incontinence patients as compared to the healthy women. Keywords Urinary incontinence, Urodynamic study, Cystometry, Adult females.